2020
DOI: 10.1016/j.neurobiolaging.2020.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Optimized prediction of cognition based on brain morphometry across the adult life span

Abstract: We mapped out the combined and unique contributions of 5 different biomarkers for 2 cognitive outcomes in cognitively healthy adults. Beside associations of biomarkers with cognition in the full experimental sample, we focused on how well any such associations would persist in held-out data. Three hundred thirty-five cognitively normal participants, 20e80 years older, were included in the study. Z-scores were computed for fluid reasoning and vocabulary. The following imaging data were included: regional brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…While results stand in contrast to findings in younger cohorts potentially due to differences in cognitive functions further aggravating only during the aging process (e.g. [ 18 , 29 ]), they fit previous accounts in studies across the lifespan and older cohorts [ 10 , 51 , 52 ]. For instance, Feng, Wang [ 52 ] revealed that language functions could be predicted to a considerably smaller degree than attention and executive functions from SC data in two large older cohorts, i.e.…”
Section: Discussionsupporting
confidence: 82%
“…While results stand in contrast to findings in younger cohorts potentially due to differences in cognitive functions further aggravating only during the aging process (e.g. [ 18 , 29 ]), they fit previous accounts in studies across the lifespan and older cohorts [ 10 , 51 , 52 ]. For instance, Feng, Wang [ 52 ] revealed that language functions could be predicted to a considerably smaller degree than attention and executive functions from SC data in two large older cohorts, i.e.…”
Section: Discussionsupporting
confidence: 82%
“…A multimodal approach, however, may allow for a more complete description of age-related cognitive decline than each single modality as aging has been found to affect the brain at all levels [ 67 ]. Initial encouraging results in different samples have demonstrated that the use of multimodal data may improve prediction performance for different cognitive abilities, e.g., fluid intelligence, global cognitive function, visual working memory, fluid reasoning, vocabulary [ 26 , 31 , 33 , 55 , 68 ]. For example, multimodal models, including information from structural and functional imaging, yielded improved prediction accuracies of up to R 2 = 0.05 compared to R 2 = 0.02–0.04 in unimodal models for fluid intelligence in a large sample from the UK Biobank [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Language functions, thus, not only appear to differ in aging trajectories (e.g., tend to remain more stable than for example executive and memory functions), but also in their predictability to other cognitive domains, e.g., processing speed, memory and executive functions, in older aged individuals [ 97 ]. A potential explanation may be that factors like education or occupational attainment may be highly relevant for the prediction of language-related cognitive performance overshadowing the predictive utility of brain features [ 26 , 98 ]. This is also supported by the feature importance analyses in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations